An assessment of the service quality expectations and perceptions of the patients of Awali Hospital in the Kingdom of Bahrain - Luke, Gary Joseph (Rhodes University, Faculty of Commerce, Investec Business School, 2008)
The quality of service from a hospital is the number one factor that will either turn a customer/patient away or make one for life. More and more hospitals are competing for greater shares in the market and customer-driven quality management is becoming the preferred method for improving their performance. Awali hospital is a private hospital in the Kingdom of Bahrain. It is a small 35-bed hospital that offers private medical services to the public. The hospital was originally built to serve the Bahrain Petroleum Company (Bapco) refinery workers but later opened its doors to the public. With the introduction of private patients came higher expectations of quality and higher demands on the overall services. A number of service quality shortfalls were identified over the years but never identified quantitatively by a patient evaluation survey. An English and Arabic version of the questionnaire based on SERVQUAL (Zeithaml, Parasuraman and Berry, 1988) was developed and placed in Awali hospital to test these service quality shortfalls. This study intends to evaluate these areas by answering questions about the relevant areas of service provided by the hospital. It measured patient satisfaction by looking at human aspects of service (responsiveness, reliability, empathy and assurance) with only one factor of the instrument being devoted to the non-human aspect of care rendered (tangibles). The SERVQUAL instrument has five dimensions that were measured by 21 pairs of item statements. One statement from each pair reflects perceptions, the other expectations. Measurement was accomplished by subtracting expectation from perceptions resulting in a service quality score. Positive or zero scores would reflect ideal or adequate service quality offered by the hospital. A negative score would be indicative of a service experience that did not meet customer expectations. Using the SERVQUAL questionnaire provided, quantifiable reasoning to the research questions in each dimension could be obtained so that precision, objectivity and rigour replaced hunches, experience and intuition as a means of investigating problem areas. Customers were first asked to supply some additional demographic information, for example gender, number of hospital visits, nationality, patient type (Bapco worker, general practitioner referred or private) and type of visit (inpatient, outpatient or both). They werethen asked to rate the hospital service on a 7-point Likert scale ranging from Strongly Agree (7) to Strongly Disagree (1). At the end of the questionnaire was space to write open comments. In total 600 paper questionnaires were distributed in the hospital, 300 English and 300 Arabic. Another 150 electronic questionnaires via emails were sent to refinery workers. Of the total 750 questionnaires distributed 162 were returned of which 156 (or 21.6%) could be statistically analysed. The empirical data results showed that the perception scores were significantly different at the p < 0.05 level from expectation scores. All the service quality differences (SQ=P-E) were negatively scored. This indicated that patients were not satisfied in all five dimensions of services offered by the hospital. Of the five dimensions responsiveness had the largest difference with assurance and reliability following with no significant differences between them. The demographic information revealed some interesting differences between the groups. Of all the demographic groups the most significant differences were between groups, "patient types" and "types of visit" , which showed differences between private patients and refinery workers and patients who used the hospital only as an outpatient and patients who used both services, outpatient and inpatient. In terms of the managerial implications, it was recommended that Awali hospital look to closing Gaps 1-4 of the SERVQUAL gap model which would result in closing the consumer gap, Gap 5. A process model for continuous measurement and improvement of service quality was recommended that looks at asking questions about how the hospital is performing. By adopting some of the recommendations identified in the research questions, Awali hospital could improve their quality of service, and as a consequence, their customer satisfaction and loyalty.
Keywords: Awali Hospital; Hospitals, Proprietary -- Bahrain; Hospital care -- Quality control -- Bahrain; Hospital care -- Evaluation -- Bahrain; Customer services -- Rating of -- Bahrain; Quality assurance